2016
DOI: 10.2196/games.4977
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Playing a Serious Computer Game on Body Mass Index and Nutrition Knowledge in Women

Abstract: BackgroundObesity and weight gain is a critical public health concern. Serious digital games are gaining popularity in the context of health interventions. They use persuasive and fun design features to engage users in health-related behaviors in a non-game context. As a young field, research about effectiveness and acceptability of such games for weight loss is sparse.ObjectiveThe goal of this study was to evaluate real-world play patterns of SpaPlay and its impact on body mass index (BMI) and nutritional kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…However, in the literature, there are studies reporting that children’s eating habits and health related self-management behaviors are improved, and even BMI is reduced by using digital games. 16 , 17 There are also contradictory studies reporting that digital games increase BMI in children. 18 Mannickko et al 11 in their study found no relationship between digital game addiction and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the literature, there are studies reporting that children’s eating habits and health related self-management behaviors are improved, and even BMI is reduced by using digital games. 16 , 17 There are also contradictory studies reporting that digital games increase BMI in children. 18 Mannickko et al 11 in their study found no relationship between digital game addiction and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Serious gaming is an umbrella term for computer-delivered interventions that provide training and education in an entertaining way [ 12 ]. This innovative tool is increasingly applied in healthcare practice [ 12 , 13 ], and recent studies in the food-related health domain have provided preliminary evidence for its effectiveness in optimizing food-related outcomes, including food intake [ 14 16 ]. A meta-analysis on the effects of serious gaming on healthy lifestyle indicated heterogeneous results, however, which can be at least partially due to the fact that serious games often lack evidence-based interventions [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In public health, these include smoking cessation [17] and diet and exercise [18]. Web-based tools such as Twitter and social media have also been used to raise awareness and educate about antibiotics [19,20].…”
Section: Introductionmentioning
confidence: 99%